Cheaper children, more children - Eva Mörk; Anna Sjögren; Helena Svaleryd (Institute for Labour Market Policy Evaluation (IFAU), 2008)
We study the effect of child care costs on the fertility behavior of Swedish women and find that reductions in child care charges influence fertility decisions, even when costs are initially highly subsidized. Exploiting the exogenous variation in child care costs caused by a Swedish child care reform, we are able to identify the causal effect of child care costs on fertility in a context in which child care enrolment is almost universal and the labor force participation of mothers is very high. A typical household planning another child experienced a reduction in expected future child care costs of SEK 106,000 (USD 17,800). This reduction resulted in 3-5 more child births per 1,000 women during an 18 month period, which corresponds to a 4-6 per cent increase in the birth rate.
Keywords: H31; J13; 330; Child care; Cost of children; Fertility; Quasi-experiment; Difference-in-differences; Familienplanung; Familienpolitik; Kinderbetreuung; Subvention; Fruchtbarkeit; Schweden